ESL Learners’ Perceptions of Online Learning in a Tertiary Institute - Shamala Benjamin Jeyaraja, Shereen; Maniam, Mahendran (International Journal of English Language Education, 2022)
The study explores how learners view the benefits and challenges faced in implementing online learning in ESL classrooms. 53 learners from a private university in Petaling Jaya, Malaysia, were selected to be participants. An adapted questionnaire from a previous study was used to collect data via the Google form. This study employs a quantitative methodology, and the SPSS software was used to analyse the data collected. The findings showed that most learners acknowledged that the introduction of online learning caused obstacles for them. The results reflected learners’ unbiased views on the benefits of integrating online learning into ESL institutions. The learners also have difficulty in learning online, and lecturers need to adapt their teaching methods and techniques to address this issue. The study recommends that online learning requires improved resources and technological support from the institution’s management.